Effect of Localized Temperature Difference on Hydrogen Fermentation - Seongwon Im (MDPI AG, 2021)
In a lab-scale bioreactor system, (20 L of effective volume in our study) controlling a constant temperature inside bioreactor with a total volume 25 L is a simple process, whereas it is a complicated process in the actual full-scale system. There might exist a localized temperature difference inside the reactor, affecting bioenergy yield. In the present work, the temperature at the middle layer of bioreactor was controlled at 35 °C, while the temperature at top and bottom of bioreactor was controlled at 35 ± 0.1, ±1.5, ±3.0, and ±5.0 °C. The H2 yield of 1.50 mol H2/mol hexoseadded was achieved at ±0.1 and ±1.5 °C, while it dropped to 1.27 and 0.98 mol H2/mol hexoseadded at ±3.0 and ±5.0 °C, respectively, with an increased lactate production. Then, the reactor with automatic agitation speed control was operated. The agitation speed was 10 rpm (for 22 h) under small temperature difference (<±1.5 °C), while it increased to 100 rpm (for 2 h) when the temperature difference between top and bottom of reactor became larger than ±1.5 °C. Such an operation strategy helped to save 28% of energy requirement for agitation while producing a similar amount of H2. This work contributes to facilitating the upscaling of the dark fermentation process, where appropriate agitation speed can be controlled based on the temperature difference inside the reactor.